Clinical characteristics of importance to outcome in patients with axial spondyloarthritis: protocol for a prospective descriptive and exploratory cohort study. Issue 7 (10th July 2017) - Andreasen, Rikke Asmussen; Kristensen, Lars Erik; Ellingsen, Torkell; Christensen, Robin; Baraliakos, Xenofon; Wied, Jimmi; Aalykke, Claus; Ulstrup, Thomas; Schiøttz-Christensen, Berit; Horn, Hans Christian; Emamifar, Amir; Duerlund, Bent; et al.
Abstract : Introduction: Spondyloarthritis (SpA) is a heterogeneous spectrum of rheumatic diseases with either predominantly axial inflammatory symptoms of the spine and sacroiliac joints or predominantly peripheral arthritis. The two main entities of axial SpA (axSpA) are ankylosing spondylitis or non-radiographic axSpA (nr-axSpA). Tumour necrosis factor-α inhibitors have revolutionised the treatment of patients with axSpA who failed to respond to non-steroidal anti-inflammatory drugs and physical therapy. Chronic pain is common in patients with SpA and may still persist despite the lack of signs of inflammation. This has led researchers to hypothesise that central pain sensitisation may play a role in the generation of chronic pain in SpA. The painDETECT Questionnaire (PDQ) is a screening tool developed to detect neuropathic pain components. The primary objective is to explore the prognostic value of the PDQ regarding treatment response in patients with axSpA 3 months after initiating a biological agent. Secondary aim is to evaluate the impact of extra-articular manifestations, comorbidities and patient-reported outcomes and elucidate if these factors influence treatment response. Method and analysis: We will include 60 participants (≥18 years of age) diagnosed with axSpA independent of main entity, who initiate or switch treatment of a biologic. Data will be collected at baseline and at endpoint following Danish clinical practice (≥3 months) of treatment with biologics. We will explore whether the PDQ and other phenotypical patient characteristics are prognostically important for response to biological therapy according to established response criteria like 50% improvement in the Bath Ankylosing Spondylitis Disease Activity Index (50%) and Ankylosing Spondylitis Disease Activity Score. Ethics and dissemination: The study is approved by the Region of Southern Denmark's Ethics committee (S-20160094) and has been designed in cooperation with patient representatives. The study is registered at clinicaltrials.gov (NCT02948608, pre-results). Dissemination will occur through publication(s) in international peer-reviewed journal(s).